Connection method for surface micro-configuration silicon nitride ceramic / nickel-based high-temperature alloy joint
By performing high-energy laser treatment on the surface of silicon nitride ceramics to form a microstructure structure and brazing with nickel-based high-temperature alloy in a vacuum heating furnace, the thermal physical properties of silicon nitride ceramic/nickel-based high-temperature alloy joints are solved due to the base material. The residual stress problems caused by the difference have improved the high strength and high temperature resistance of the joint.
Patent Information
- Application Number
- CN202411484112.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The silicon nitride ceramic/nickel-based high-temperature alloy joints have residual stress problems due to excessive differences in thermal physical properties of the base material, resulting in poor microcracks and mechanical properties.
By performing high-energy laser treatment on the surface of silicon nitride ceramics, it is formed into a microstructure structure and brazed with nickel-based high-temperature alloy in a vacuum heating furnace. The intermediate layer metal structure and adhesive are used to form a tight fit to ensure the interfacial reactants The formation and adhesive volatilization are achieved to achieve a good combination of ceramics and metals.
It effectively improves the strength and high temperature resistance of the joints, reduces residual stress, and realizes high-strength connection between ceramics and metals. It has a simple process and no impurity elements are introduced.
Smart Images

Figure CN119304297A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a connection method for a silicon nitride ceramic / nickel-based high-temperature alloy joint. Background Art
[0002] Silicon nitride ceramics have the excellent properties of low density and high strength and are widely used in the aerospace field. However, due to the brittleness of the ceramic material itself, it is difficult to process it into complex large components. The preparation of ceramic-metal dissimilar material connectors helps to give full play to its excellent performance. Nickel-based high-temperature alloys (GH4169) are regarded as excellent structural materials in the high-temperature field because of their high high-temperature performance and easy processing and forming. However, the biggest difficulty in obtaining high-performance dissimilar material joints is the residual stress problem caused by the large difference in the thermal physical properties of the parent material, which leads to microcracks in the joints and poor mechanical properties. Summary of the invention
[0003] The present invention aims to solve the technical problem that the current silicon nitride ceramic / nickel-based high-temperature alloy joints will generate residual stress, resulting in microcracks in the connected joints and poor mechanical properties, and provide a connection method for silicon nitride ceramic / nickel-based high-temperature alloy joints with surface micro-configuration.
[0004] The connection method of the silicon nitride ceramic / nickel-based high-temperature alloy joint for surface micro-configuration of the present invention is carried out according to the following steps:
[0005] 1. Preparation of silicon nitride surface microstructure:
[0006] 1. Grind the surface of the silicon nitride ceramic block to be welded on a 400# diamond grinding disc until the surface of the sample is flat, then grind it on a flat glass with W3.5 diamond grinding paste until there is no obvious wire cutting mark on the surface of the silicon nitride ceramic block to be welded, and then grind it with W1 grinding paste until the surface of the silicon nitride ceramic block to be welded is bright;
[0007] 2. Placing the bright silicon nitride under a laser, and obtaining a microstructure on the surface of the silicon nitride under the action of the high-energy laser, namely the silicon nitride mother material; the microstructure is a cone array structure or a cylinder array structure;
[0008] 2. Placing the intermediate layer metal and the silicon nitride base material obtained in step 1 on the surface of the nickel-based high-temperature alloy to be welded in sequence, and applying adhesive between the layers to form a tight fit to obtain a workpiece to be welded;
[0009] The structure of the intermediate layer metal is: Ti foil / Cu foil / Ni foil / MoCu foil / Ni foil / Cu foil, wherein the Ti foil is located close to the silicon nitride base material, and adhesive is applied between the layers to form a tight fit;
[0010] 3. Place the workpiece to be welded assembled in step 2 into a vacuum heating furnace, raise the temperature from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the adhesive is completely volatilized; then raise the temperature from 300℃~310℃ to 1080~1160℃ and keep it warm for 5min~20min, then slowly cool it down to 300℃~310℃, and finally cool it to room temperature with the furnace to complete the brazing of ceramic and metal. The whole process is carried out under vacuum.
[0011] In the present invention, in step 1, the surface of silicon nitride is processed by laser to construct micro-structures, and micro-structures with different morphologies are designed, which can effectively increase the final joint surface area and improve the distribution of joint residual stress, and can improve the joint strength. Under the action of high-energy laser, the Si-N bond of silicon nitride is broken, N is separated in the form of N2, and the molten Si is cooled and solidified on the surface of the micro-structure; laser treatment does not introduce impurity elements, especially oxygen elements, and no SiO2 layer is formed on the surface after laser treatment. The Si element directly reacts with the active element Ti to generate sufficient interface reactants, ensuring good bonding between silicon nitride and the weld.
[0012] The present invention aims to obtain a ceramic-high temperature alloy joint with a good interface, and obtains a high temperature resistant joint by surface treating silicon nitride-GH4169 through partial instantaneous liquid phase connection, thereby realizing a silicon nitride ceramic / GH4169 alloy high temperature resistant joint. The present invention has a simple process, and can effectively improve the connection strength of the joint by laser processing the silicon nitride ceramic surface, thereby realizing a high-strength connection between ceramic and metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the SEM image of the silicon nitride base material obtained in step 1 of experiment 1;
[0014] Figure 2 The XRD image of the silicon nitride base material obtained in step 1 of experiment 1;
[0015] Figure 3 The Raman spectrum of the silicon nitride base material obtained in step 1 of experiment 1;
[0016] Figure 4 This is the SEM photo of the joint structure obtained in Experiment 1;
[0017] Figure 5 for Figure 4 EDS analysis results of the corresponding positions in;
[0018] Figure 6 This is a photo of the element surface distribution on the silicon nitride side of the joint obtained in Experiment 1;
[0019] Figure 7 This is the SEM image of the silicon nitride base material obtained in step 1 of experiment 4. DETAILED DESCRIPTION
[0020] Specific implementation method 1: This implementation method is a connection method for silicon nitride ceramic / nickel-based high-temperature alloy joints with surface micro-structures, which is specifically carried out in the following steps:
[0021] 1. Preparation of silicon nitride surface microstructure:
[0022] 1. Grind the surface of the silicon nitride ceramic block to be welded on a 400# diamond grinding disc until the surface of the sample is flat, then grind it on a flat glass with W3.5 diamond grinding paste until there is no obvious wire cutting mark on the surface of the silicon nitride ceramic block to be welded, and then grind it with W1 grinding paste until the surface of the silicon nitride ceramic block to be welded is bright;
[0023] 2. Placing the bright silicon nitride under a laser, obtaining a microstructure on the surface of the silicon nitride under the action of a high-energy laser, and then performing ultrasonic cleaning to obtain a silicon nitride mother material; the microstructure is a cone array structure or a cylinder array structure;
[0024] 2. Placing the intermediate layer metal and the silicon nitride base material obtained in step 1 on the surface of the nickel-based high-temperature alloy to be welded in sequence, and applying adhesive between the layers to form a tight fit to obtain a workpiece to be welded;
[0025] The structure of the intermediate layer metal is: Ti foil / Cu foil / Ni foil / MoCu foil / Ni foil / Cu foil, wherein the Ti foil is located close to the silicon nitride base material, and adhesive is applied between the layers to form a tight fit;
[0026] 3. Place the workpiece to be welded assembled in step 2 into a vacuum heating furnace, raise the temperature from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the adhesive is completely volatilized; then raise the temperature from 300℃~310℃ to 1080~1160℃ and keep it warm for 5min~20min, then slowly cool it down to 300℃~310℃, and finally cool it to room temperature with the furnace to complete the brazing of ceramic and metal. The whole process is carried out under vacuum.
[0027] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the laser in step 12 is a femtosecond laser. The rest is the same as specific implementation method 1.
[0028] Specific implementation method three: This implementation method is different from specific implementation method two in that the parameters of the high-energy laser in step 12 are: laser frequency is 200kHz to 250kHz, scanning speed is 500mm / s to 600mm / s, laser beam size is 30μm to 40μm, laser power is 12W to 15W, and wavelength is 355nm to 455nm. Others are the same as specific implementation method two.
[0029] Specific implementation method 4: This implementation method is different from the specific implementation methods 1 to 3 in that the nickel-based high-temperature alloy needs to be surface cleaned before step 2. The rest is the same as the specific implementation methods 1 to 3.
[0030] Specific embodiment 5: This embodiment is different from the specific embodiment 4 in that the process of surface cleaning of the nickel-based high-temperature alloy is as follows:
[0031] The oxide layer and visible rough scratches on the surface of the nickel-based alloy to be welded are treated with water sandpaper, and then the surface to be welded is polished with 600, 800, and 1000 metallographic sandpapers in sequence until there are no obvious scratches on the surface to be welded, and finally polished with diamond particles with a particle size of 0.5 μm to make the surface to be welded bright, and then ultrasonic cleaning is performed. The rest is the same as the specific implementation method four.
[0032] Specific implementation method 6: This implementation method is different from the specific implementation method 5 in that the adhesives mentioned in the two places in step 2 are both 502 adhesives. The rest is the same as the specific implementation method 5.
[0033] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that: in step 3, when the temperature reaches above 750°C, the vacuum degree must be ensured to be within 1×10 -2 Pa or less. Other aspects are the same as those of the sixth embodiment.
[0034] Specific embodiment eight: This embodiment differs from specific embodiment seven in that in step three, the temperature is raised from room temperature to 300°C to 310°C at a heating rate of 10°C / min and kept at that temperature for 30min to 35min to ensure that the adhesive is completely volatilized. The rest is the same as specific embodiment seven.
[0035] Specific embodiment 9: This embodiment differs from specific embodiment 8 in that in step 3, the temperature is subsequently raised from 300°C to 310°C to 1080°C to 1160°C at a heating rate of 10°C / min and kept at that temperature for 5min to 20min. The rest is the same as specific embodiment 8.
[0036] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that in step 3, the temperature is slowly lowered to 300°C to 310°C at 5°C / min, and finally cooled to room temperature with the furnace to complete the brazing of ceramic and metal, and the whole process is carried out under vacuum. Other aspects are the same as specific embodiment 9.
[0037] The present invention is verified by the following tests:
[0038] Test 1: This test is a connection method for silicon nitride ceramic / nickel-based high-temperature alloy joints with surface micro-structures, which is specifically carried out in the following steps:
[0039] 1. Preparation of silicon nitride surface microstructure:
[0040] 1. Grind the surface of the silicon nitride ceramic block to be welded on a 400# diamond grinding disc until the surface of the sample is flat, then grind it on a flat glass with W3.5 diamond grinding paste until there is no obvious wire cutting mark on the surface of the silicon nitride ceramic block to be welded, and then grind it with W1 grinding paste until the surface of the silicon nitride ceramic block to be welded is bright;
[0041] 2. Place the bright silicon nitride under a femtosecond laser, obtain a microstructure on the surface of the silicon nitride under the action of a high-energy laser, and then perform ultrasonic cleaning with anhydrous ethanol for 10 minutes to obtain a silicon nitride matrix; the microstructure is a conical array structure, wherein the radius of the unit structure is 40 μm, the height is 15 μm, and the array unit interval is 100 μm (such as Figure 1 shown);
[0042] The parameters of the high-energy laser are: laser frequency of 200kHz, scanning speed of 500mm / s, laser beam size of 30μm, laser power of 12W, and wavelength of 355nm;
[0043] 2. Treat the oxide layer and visible rough scratches on the surface of the metal base material nickel-based alloy GH4169 to be welded with water sandpaper, then polish with metallographic sandpaper No. 600, 800, and 1000 in sequence until there are no obvious scratches on the surface to be welded, finally polish with diamond particles with a particle size of 0.5 μm to make the surface to be welded bright, and then perform ultrasonic cleaning with anhydrous ethanol for 10 minutes; place the intermediate layer metal and the silicon nitride base material obtained in step 1 on the surface to be welded of the nickel-based high-temperature alloy GH4169 in sequence, apply adhesive between the layers to form a tight fit, and obtain a workpiece to be welded;
[0044] The structure of the intermediate layer metal is: Ti foil / Cu foil / Ni foil / MoCu foil / Ni foil / Cu foil, wherein the Ti foil is located close to the silicon nitride base material, and adhesive is applied between the layers to form a tight fit;
[0045] The adhesives mentioned in both places in step 2 are 502 glue;
[0046] 3. Put the workpiece to be welded assembled in step 2 into a vacuum heating furnace, heat it from room temperature to 300℃ at a heating rate of 10℃ / min and keep it warm for 30min to ensure that the adhesive is completely volatilized; then heat it from 300℃ to 1100℃ at a heating rate of 10℃ / min and keep it warm for 10min, then slowly cool it to 300℃ at 5℃ / min, and finally cool it to room temperature with the furnace to complete the brazing of silicon nitride ceramics and nickel-based high-temperature alloy GH4169. The whole process is carried out under vacuum. When the temperature reaches above 750℃, the vacuum degree must be ensured to be 1×10 -2Below Pa.
[0047] After the connection was completed, there were no obvious microcracks in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint was 142 MPa.
[0048] Figure 1 This is the SEM image of the silicon nitride base material obtained in step 1 of experiment 1, indicating that the laser treatment obtains a uniform cone array structure, in which the radius of the unit structure is 40 μm, the height is 15 μm, and the array unit spacing is 100 μm.
[0049] Figure 2 The XRD image of silicon nitride parent material obtained in step 1 of experiment 1. Since the residual silicon layer is thin, XRD will penetrate, and the signal of silicon nitride in the parent material is the strongest, which will cover the signal of Si, so the peaks shown in the figure are all silicon nitride peaks. Therefore, Raman is used for micro-area characterization. Figure 3 The Raman spectrum of the silicon nitride base material was obtained in step 1 of experiment 1. The Raman results showed that the laser treatment did not introduce impurities. Only the Si peak was detected after the laser treatment, verifying that the molten Si element cooled and solidified on the modified surface.
[0050] Figure 4 This is the SEM photo of the joint structure obtained in Test 1. The picture shows that the joint is well bonded and no obvious defects are found.
[0051] Figure 5 for Figure 4 From the EDS analysis results of the corresponding positions in the joint, it can be seen that the microstructure of the joint is a copper-based solid solution containing a small amount of Ni element and a dispersed Ti-Cu intermetallic compound phase.
[0052] Figure 6 This is a photograph of the element surface distribution on the silicon nitride side of the joint obtained in Experiment 1. It can be seen that the Ti element is enriched in the interface reaction layer, with only a small amount of copper-based solid solution dispersed, and the Cu and Ni elements are enriched in the weld.
[0053] Experiment 2: This experiment is different from Experiment 1 in that:
[0054] The parameters of the high-energy laser in step 1-2 are different. The microstructure obtained in step 1 is a cone array structure, in which the radius of the unit structure is 30 μm, the height is 20 μm, and the array unit interval is 120 μm;
[0055] In step 3, the temperature is then raised from 300°C to 1120°C at a heating rate of 10°C / min and kept at this temperature for 5 minutes. The rest is the same as in experiment 1. After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint is 54MPa.
[0056] Test 3: This test is different from Test 1 in that:
[0057] The parameters of the high-energy laser in step 1-2 are different. The microstructure obtained in step 1 is a cone array structure, in which the radius of the unit structure is 20 μm, the height is 10 μm, and the array unit interval is 100 μm; the rest is the same as experiment 1. After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint is 96 MPa.
[0058] Test 4: This test is different from Test 1 in that:
[0059] The parameters of the high-energy laser in step 1-2 are different. The specific parameters of the laser are as follows: frequency is 200kHz, scanning speed is 400mm / s, laser beam size is 30μm, laser power is 14W, and wavelength is 350nm; the microstructure obtained in step 1 is a cylindrical array structure, in which the radius of the unit structure is 35μm, the height is 40μm, and the array unit spacing is 80μm (such as Figure 7 The other parts are the same as those in Test 1. After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint is 94MPa.
Claims
1. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure, characterized in that The connection method for silicon nitride ceramic / nickel-based high-temperature alloy joints with surface micro-texture is carried out in the following steps:
1. Preparation of silicon nitride surface microstructure: ①. Grind the surface of the silicon nitride ceramic block to be welded on a 400# diamond grinding disc until the surface of the sample is flat, then grind it on a flat piece of glass with W3.5 diamond grinding paste until there is no obvious wire cutting mark on the surface of the silicon nitride ceramic block to be welded, and then grind it with W1 grinding paste until the surface of the silicon nitride ceramic block to be welded is bright; ②, placing the bright silicon nitride under a laser, obtaining a microstructure on the surface of the silicon nitride under the action of a high-energy laser, and then performing ultrasonic cleaning to obtain a silicon nitride mother material; the microstructure is a cone array structure or a cylinder array structure; 2. Placing the intermediate layer metal and the silicon nitride base material obtained in step 1 on the surface of the nickel-based high-temperature alloy to be welded in sequence, and applying adhesive between the layers to form a tight fit to obtain a workpiece to be welded; The structure of the intermediate layer metal is: Ti foil / Cu foil / Ni foil / MoCu foil / Ni foil / Cu foil, wherein the Ti foil is located close to the silicon nitride base material, and adhesive is applied between the layers to form a tight fit; 3. Place the workpiece to be welded assembled in step 2 into a vacuum heating furnace, raise the temperature from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the adhesive is completely volatilized; then raise the temperature from 300℃~310℃ to 1080~1160℃ and keep it warm for 5min~20min, then slowly cool it down to 300℃~310℃, and finally cool it to room temperature with the furnace to complete the brazing of ceramic and metal. The whole process is carried out under vacuum.
2. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 1, characterized in that The laser described in step 1② is a femtosecond laser.
3. A connection method for a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 2, characterized in that The parameters of the high-energy laser described in step 1② are: laser frequency of 200kHz to 250kHz, scanning speed of 500mm / s to 600mm / s, laser beam size of 30μm to 40μm, laser power of 12W to 15W, and wavelength of 355nm to 455nm.
4. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 1, characterized in that The nickel-based high-temperature alloy must be surface cleaned before step 2.
5. A connection method for a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 4, characterized in that The process of surface cleaning of the nickel-based high-temperature alloy is as follows: Use water sandpaper to treat the oxide layer and visible rough scratches on the surface of the metal base material nickel-based alloy to be welded, and then use 600, 800, and 1000 metallographic sandpapers in turn to grind until there are no obvious scratches on the surface to be welded. Finally, polish with diamond particles with a particle size of 0.5μm to make the surface to be welded bright, and then perform ultrasonic cleaning. The rest is the same as the fourth specific implementation method.
6. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 1, characterized in that The adhesives described in two places in step 2 are both 502 glue.
7. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 1, characterized in that In step 3, when the temperature reaches above 750°C, the vacuum degree must be maintained at 1×10 -2 Below Pa.
8. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 7, characterized in that In step 3, the temperature is raised from room temperature to 300°C to 310°C at a heating rate of 10°C / min and kept at this temperature for 30min to 35min to ensure that the adhesive is completely volatilized.
9. A method for connecting a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 8, characterized in that In step three, the temperature is then increased from 300°C to 310°C to 1080°C to 1160°C at a heating rate of 10°C / min and maintained for 5min to 20min.
10. A connection method for a silicon nitride ceramic / nickel-based high-temperature alloy joint with a surface microstructure according to claim 9, characterized in that In step three, the temperature is slowly lowered to 300°C to 310°C at 5°C / min, and finally cooled to room temperature with the furnace to complete the brazing of the ceramic and the metal. The entire process is carried out under vacuum.
Citation Information
Patent Citations
Silicon nitride ceramic surface modification assisted direct diffusion bonding method
CN111320487A
Connection method of silicon nitride ceramic / nickel-based superalloy
CN114211076A
Silicon nitride ceramic copper-clad substrate and preparation method thereof
CN114230361A
Silicon carbide pre-welding surface treatment method and silicon carbide and high-temperature alloy welding method
CN116161985A
Laser processing method for Ti2AlNb super-lyophilic microstructure
CN117047287A